2015
DOI: 10.1080/02724634.2015.981636
|View full text |Cite
|
Sign up to set email alerts
|

New fossil species of the extant genusLepidobatrachus(Anura, Ceratophryidae) from the Late Miocene-Early Pliocene of central Argentina

Abstract: Taylor & Francis makes every effort to ensure the accuracy of all the information (the "Content") contained in the publications on our platform. However, Taylor & Francis, our agents, and our licensors make no representations or warranties whatsoever as to the accuracy, completeness, or suitability for any purpose of the Content. Any opinions and views expressed in this publication are the opinions and views of the authors, and are not the views of or endorsed by Taylor & Francis. The accuracy of the Content s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Chaco wooded areas were also recovered at Farola Monte Hermoso (Tonni, 1974;Tomassini et al, 2011;Nicoli, 2015), supporting the idea that at least until the Pliocene, the climatic conditions on Farola Monte Hermoso were similar to those of the current Chaco (Tonni, 1974;Pascual, 1984;Pascual et al, 1996). Nicoli (2015) questioned some of the paleoecological inferences of these authors, especially those based on the presence of fossils of widely distributed species (extant or extinct), which occur in other regions besides the Chaco. However, the presence of fossils of species that currently are not restricted to the Gran Chaco is not ultimate evidence that Farola Monte Hermoso was not similar to the current Chaco.…”
Section: Fst Damentioning
confidence: 63%
See 2 more Smart Citations
“…Chaco wooded areas were also recovered at Farola Monte Hermoso (Tonni, 1974;Tomassini et al, 2011;Nicoli, 2015), supporting the idea that at least until the Pliocene, the climatic conditions on Farola Monte Hermoso were similar to those of the current Chaco (Tonni, 1974;Pascual, 1984;Pascual et al, 1996). Nicoli (2015) questioned some of the paleoecological inferences of these authors, especially those based on the presence of fossils of widely distributed species (extant or extinct), which occur in other regions besides the Chaco. However, the presence of fossils of species that currently are not restricted to the Gran Chaco is not ultimate evidence that Farola Monte Hermoso was not similar to the current Chaco.…”
Section: Fst Damentioning
confidence: 63%
“…6). A fossil of a recently described species of Lepidobatrachus (Nicoli, 2015) was found at Farola Monte Hermoso, province of Buenos Aires (Tomassini et al, 2011). This locality corresponds to Rio de la Plata Craton.…”
Section: Fst Damentioning
confidence: 95%
See 1 more Smart Citation
“…Specimen assigned to Wawelia geroldhi , from Miocene sediments of northern Patagonia in Argentina [ 16 ], seems to represent a juvenile anuran with some features like extant ceratophryids. Other late Miocene specimens have been attributed to Ceratophrys [ 17 – 20 ] and Lepidobatrachus [ 21 , 22 ]. Those specimens, plus independent molecular data [ 5 , 23 ], indicated that both genera were well differentiated by the Miocene.…”
Section: Introductionmentioning
confidence: 99%
“…The fossil record of Ceratophryidae dates back to the Late Miocene and it is quite rich compared with the scarce fossil record of most other neotropical anuran groups (Barcelos & dos Santos, 2022;Gómez et al, 2013;Pérez-Ben et al, 2019a, b;Turazzini et al, 2016). Despite the broad South American distribution of extant forms, fossils are largely concentrated in the Argentinean Pampas and consist mostly of variably complete cranial remains and comparatively few, mainly isolated, postcranial bones of Ceratophrys (Agnolin, 2005;Barcelos et al, 2020;Fernicola, 2001;Gómez & Turazzini, 2021;Marshall & Patterson, 1981;Nicoli, 2016Nicoli, , 2017Nicoli, , 2019Peri, 1993;Stoessel et al, 2008), whereas no fossils are known for Chacophrys, and only three specimens, including the one described herein, have been identified as Lepidobatrachus so far (Gómez & Turazzini, 2021;Nicoli, 2015;Tomassini et al, 2011;Turazzini, 2015).…”
Section: Introductionmentioning
confidence: 99%